2022
DOI: 10.1186/s12870-022-03898-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative chloroplast genome analyses of Amomum: insights into evolutionary history and species identification

Abstract: Background Species in genus Amomum always have important medicinal and economic values. Classification of Amomum using morphological characters has long been a challenge because they exhibit high similarity. The main goals of this study were to mine genetic markers from cp genomes for Amomum species identification and discover their evolutionary history through comparative analysis. Results Three species Amomum villosum, Amomum maximum and Amomum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Thus, a ratio of Ka/Ks < 1 indicates purifying selection, Ka/Ks > 1 denotes probable positive selection, and Ka/Ks values close to one indicate neutral evolution. In this study, the majority of the protein-coding genes of Datureae species were found to be under purifying selection by Ka/Ks analysis, which was conservative in plastid genomes of most angiosperms ( Gong et al., 2022 ). However, we found that 31 cp genes might be under positive selection during the evolution process; these genes are connected to proteins from ATP subunit, photosystem subunit, ribosome large subunit, NAD(P)H dehydrogenase complex, and other genes such as clp P, pet B, rbc L, rpo C1, ycf 4, and cem A.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, a ratio of Ka/Ks < 1 indicates purifying selection, Ka/Ks > 1 denotes probable positive selection, and Ka/Ks values close to one indicate neutral evolution. In this study, the majority of the protein-coding genes of Datureae species were found to be under purifying selection by Ka/Ks analysis, which was conservative in plastid genomes of most angiosperms ( Gong et al., 2022 ). However, we found that 31 cp genes might be under positive selection during the evolution process; these genes are connected to proteins from ATP subunit, photosystem subunit, ribosome large subunit, NAD(P)H dehydrogenase complex, and other genes such as clp P, pet B, rbc L, rpo C1, ycf 4, and cem A.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have indicated that the single plastome fragment is not suitable for the identification of several medicinal plants within the genus Amomum [55,61,63,[73][74][75][76]. The complete plastomes have demonstrated a strong capability to differentiate species of Amomum [55].…”
Section: Dna Barcoding In Six Medicinal Plants Within Amomummentioning
confidence: 99%
“…Additionally, the matK gene and the psbA-trnH intergenic spacer exhibit high identification efficiency for A. tsao-ko and other Amomum species [57]. Among them, the barcodes that are more effective for molecular identification of Amomum are ITS [57][58][59], ITS1 [60,61], and ITS2 [61][62][63]. These research findings demonstrate the promising potential application of DNA barcoding technology in species identification and classification within Amomum.…”
Section: Introductionmentioning
confidence: 95%
“…Some other aspects that are included in QC are physical examination, microscopical examination, chemical examination, microbiological examination, stability testing, toxicological examination, and a combination of the aforementioned techniques. 9 Despite these advances, adulteration and substitutions persist in the current period. These conventional pharmacognostic studies and techniques, even the use of modern hyphenated analytical systems, also failed to detect adulterants and substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, molecular biology has had a significant impact on plant science research, allowing us to uncover many previously unknown genetic and behavioral traits in plants. These genetic traits are very helpful in identifying plants of particular species in cases of adulteration and substitution. , There are several techniques available, including conventional sequencing, non-Sanger sequencing, random amplifiable polymorphic DNA, DNA barcoding, amplifiable fragment length polymorphism, microsatellites, single nucleotide polymorphism, and others. The limitation with a few of these methods is that no ideal marker exists for all the species, and sometimes, it may mislead in identifying the taxonomy but could be highly beneficial in population genetics .…”
Section: Introductionmentioning
confidence: 99%